Research on Airworthiness certification of Civil aircraft based on Digital virtual flight test technology - Liu, Xiaoqin; Xiao, Gang; Wang, Miao; Li, Hongyu (IEEE/AIAA Digital Avionics Systems Conference, 2019)
In the process of airworthiness certification for civil aircraft, safety of flight test is the primary precondition for the staff of flight test organization to carry out its work. However, in traditional flight test process, especially in the high-risk flight test subjects, means to ensure flight safety are relatively limited. In addition, the time-consuming flight test cycle and enormous testing points lead to huge time cost and economic cost of civil aircraft in the process of airworthiness certification. In order to solve the above problems, a testing compliance verification method based on digital virtual flight test technology is proposed in this paper. The method has great significance for reducing risk and ensuring safety of flight test. And the number of testing points and costs incurred in flight tests can be greatly depleted if this method is adopted. Moreover, it can also improve the scientific and efficiency of flight test. Digital flight test technology mentioned above refers to carry out human-machine closed-loop simulation of specific assessment flight task by using digital computers. It is based on the mathematical modeling of aircraft dynamics, structure, avionics system and so on, and combined with the pilot model or human-in-the-loop method. According to the simulation results, whether the operation, maneuverability and safety of aircraft flight can meet the airworthiness requirements are investigated. In view of the above idea, digital virtual flight test model and the pilot model should be established to verify the influence of the introduction of digital flight test technology, respectively. Taking stall speed subject as an example, each test point is repeated 6 times in the process of qualified certification of a certain type of aircraft, a total of 228 tests are required. If all test points are completed by means of the conformity test method and 80% of test points are re-tested at the qualification stage (another 20% are in parallel flight test), a total of 400 flight tests should be carried out to meet the requirements. If the repeat flight test points are reduced to less than 15%, the number of flight test in this subject can be reduced from 400 to 260. If the high realistic model and reliable simulation data are used as an effective supplement, the number of flight test in this subject could be reduced from 260 to 40. If only the most extreme testing point being selected for flight testing, and only 1-2 repetitions are needed for each test point, the number of flight test can be reduced from 40 to less than 10. From this set of data, it can be fully seen that using airworthiness certification method has a positive role in ensuring the safety of flight testing. It also has great significance to reduce the number of flight test points, especially for high-risk flight test subject. Meanwhile, the efficiency of airworthiness certification for civil aircraft can also be greatly improved. Therefore, the simulated result in the paper can provide important theoretical reference for civil aircraft airworthiness certification.